Student opinions regarding strengths and weaknesses of face to face and online teaching - Nayci, Ömer (Uluslararası Eğitim Programları ve Öğretim Çalışmaları Dergisi, 2020)
This qualitative case study was carried out to identify the strengths and weaknesses of face to face and online teaching. The study group of the research study consisted of a total of 47 students attending a public university, 36 of whom are female and 11 of whom are male students. In the study, semi-structured interview form wasused as the data collection tool. The data obtained within the scope of the research were analyzed by means of content analysis. When the findings were evaluated in general, it was seen that students mostly prefer face to face teaching. Besides it was also seen that both online and face to face teaching have strengths and weaknesses relative to each other. However, it has emerged that face to face teaching has more strengths than online learning. Although this view comes into prominence, online applications which are one of the important tools of accessing information in today's conditions, should also be used in the learning and teaching process. Especially in situations where face to face teaching is not available, online applications can be used as an important tool in order to establish the communication link between the learner and teacher and also to maintain learning.
Keywords: Online Learning; Face to face Teaching; Distance education